2018
DOI: 10.7150/thno.22952
|View full text |Cite
|
Sign up to set email alerts
|

The role of PTRF/Cavin1 as a biomarker in both glioma and serum exosomes

Abstract: Exosomes play critical roles in intercellular communication in both nearby and distant cells in individuals and organs. Polymerase I and transcript release factor (PTRF), also known as Cavin1, has previously been described as a critical factor in caveola formation, and aberrant PTRF expression has been reported in various malignancies. However, the function of PTRF in tumor progression remains controversial, and its role in glioma is poorly understood. In this study, we report that PTRF is associated with mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 46 publications
(51 reference statements)
1
77
0
Order By: Relevance
“…Although a significant difference was not achieved, the result showed a tendency for lower levels of CAVIN1 expression to be correlated with better patient survival (Figure C, P = 0.0574; D, P = 0.0719). Second, we found that shorter patient survival was accompanied by higher expression of CAVIN1 in patients with wild‐type EGFR (Figure E,F and Figure S6A,B), which was consistent with the findings of a recent study . Lastly, the analysis combined with MGMT promoter methylation status demonstrated that there was no significant difference in CAVIN1 expression between the groups with methylated and unmethylated promoters (Figure S6C,D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a significant difference was not achieved, the result showed a tendency for lower levels of CAVIN1 expression to be correlated with better patient survival (Figure C, P = 0.0574; D, P = 0.0719). Second, we found that shorter patient survival was accompanied by higher expression of CAVIN1 in patients with wild‐type EGFR (Figure E,F and Figure S6A,B), which was consistent with the findings of a recent study . Lastly, the analysis combined with MGMT promoter methylation status demonstrated that there was no significant difference in CAVIN1 expression between the groups with methylated and unmethylated promoters (Figure S6C,D).…”
Section: Resultsmentioning
confidence: 99%
“…The knock‐down of CAVIN1 reduces multidrug resistance in breast cancer cell line MCF‐7/ADR cells . In GBM, it has been shown that CAVIN1 mediated chemoresistance in U251 cell lines, and its expression was upregulated in samples from relapsed GBM patients, but the number of patient samples was limited . A recent study identified an eight‐gene signature, including CAVIN1 that could predict the outcome of GBM patients .…”
Section: Introductionmentioning
confidence: 99%
“…[25] Briefly, cells were lysed with radio immunoprecipitation assay (RIPA) buffer (Solarbio, Beijing, China) for total lysate extraction. [25] Briefly, cells were lysed with radio immunoprecipitation assay (RIPA) buffer (Solarbio, Beijing, China) for total lysate extraction.…”
Section: Methodsmentioning
confidence: 99%
“…7,8 In glioblastoma (GBM), caveolae or caveola-forming proteins have been proposed to be important in the regulation of EGFR signalling, resistance to treatment and exosome-mediated cell-cell communication. [9][10][11] Moreover, the expression of both caveolin-1 and CAVIN1 are increased in GBM compared to normal samples and are associated with shorter patient survival time and correlated with expression of the matrix proteases uPA and gelatinases. 12 Matrix proteases are key mediators of the invasiveness of GBM, which in turn contributes to the disease particularly poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The pressure‐sensing capabilities of caveolae and the mechanotransduction capacities of caveola‐forming proteins have pathophysiological consequences on cardiovascular or muscle function . In glioblastoma (GBM), caveolae or caveola‐forming proteins have been proposed to be important in the regulation of EGFR signalling, resistance to treatment and exosome‐mediated cell‐cell communication . Moreover, the expression of both caveolin‐1 and CAVIN1 are increased in GBM compared to normal samples and are associated with shorter patient survival time and correlated with expression of the matrix proteases uPA and gelatinases …”
Section: Introductionmentioning
confidence: 99%